Incorporating Communicative Competence in Assessment and English Language Teaching in Multilingual Settings - Yuzar, Ella (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
There has been a high level of agreement among scholars that communicative competence should be integrated within language learning and assessments. The study attempts to unravel the issues of how communicative competence can be assessed and measured in multilingual environments and how communicative language testing can be promoted. Using the content analysis approach as the qualitative method, it begins with the historical review of communicative competence that started at the beginning of 1970s to the most current concept involving intercultural communicative competence. Then, some practical models of communicative competence that can be used to propose a measurement of communicative competence are presented. Later, this article argues that there is an upsurge need to shift the paradigm of language testing and language assessment towards communicative competence. Moreover, the nature of language testing should not only concern linguistic or knowledge competence but also recognize the different varieties of English. This study implies that, in the field of language testing, language test designers should encompass the concept of communicative competence in the test construct to include real-life language use, and by extension, to increase test validity. As for teachers, a reform integrating communicative competence in classroom language assessment has become essential within the scope of language teaching.